2023
DOI: 10.1177/11786302231185683
|View full text |Cite
|
Sign up to set email alerts
|

Personal Protective Equipment Utilization and Associated Factors among Industry Park Construction Workers in Northwest Ethiopia

Abstract: Introduction: Equipment that safeguards the user from the risk of accidents or harmful health effects is known as personal protective equipment. Reports show personal protective equipment utilization is low in Africa. Workers are exposed to a wide range of physical, chemical, and incidental hazards because of low utilization of personal protective equipment. Therefore, this study aimed to assess the magnitude and factors associated with personal protective equipment utilization among Bure Industrial Park const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The prevalence of chronic symptoms in the current study was consistent with a study conducted in Malaysia, India, and Tanzania, which determined symptom levels of 24.5%, 21.4%, and 21.6% respectively [ 17 – 19 ]. In addition, the prevalence of coughing and breathlessness were similar to studies conducted in India and Iran, which found 15.5% coughing, 3.9% breathlessness, 17.8% coughing, and 2.35% breathlessness respectively [ 3 , 20 ]. Generally, the elevated prevalence of respiratory symptoms may be attributable to exposure to welding fumes in their work environment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The prevalence of chronic symptoms in the current study was consistent with a study conducted in Malaysia, India, and Tanzania, which determined symptom levels of 24.5%, 21.4%, and 21.6% respectively [ 17 – 19 ]. In addition, the prevalence of coughing and breathlessness were similar to studies conducted in India and Iran, which found 15.5% coughing, 3.9% breathlessness, 17.8% coughing, and 2.35% breathlessness respectively [ 3 , 20 ]. Generally, the elevated prevalence of respiratory symptoms may be attributable to exposure to welding fumes in their work environment.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study welders who were not given training on occupational safety were more likely to develop a chronic respiratory symptom than those who did not get training. This might be because the welders utilized RPE more effectively after the training [ 20 ].…”
Section: Discussionmentioning
confidence: 99%